Tinjauan Hukum Hak Asasi Manusia Internasional Terhadap Extrajudicial Killing - Morich Thenu; Josina Augustina Yvonne Wattimena; Johanis Steny Franco Peilouw (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: This study discusses Extrajudicial Killing which is an act of extrajudicial killing carried out at the behest of the government or other powerful parties, and the authorities have not succeeded in in-depth investigation or arresting who is the mastermind of the murder.Purposes of the Research: To find out that extrajudicial killing violates international human rights law and international legal efforts to enforce human rights as a result of extrajudicial killing in the Philippines.Methods of the Research: This research method uses a normative legal research type and an analytical perspective research type using a statutory approach, a conceptual approach and a case approach.Results of the Research: The results of the study show that the Extrajudicial killing carried out by the President of the Philippines Rodrigo Duterte by killing people suspected of abusing narcotics has killed more than 5000 (five thousand) citizens is a violation of human rights and crimes against humanity. So that the act of killing can be qualified to violate international law and is included as a crime against humanity based on the 1998 Rome Statute because it fulfills the elements of crimes against humanity in accordance with Article 7 of the 1998 Rome Statute, namely the occurrence of widespread or systematic killings carried out by state officials.